Proceso atención de enfermería en paciente de 16 años de edad con fractura de la epífisis inferior del radio. - Palomino Yánez, Lady Diana (2022)
The fracture of the inferior epiphysis of the radius, this is one of the most common bone injuries in children due to its proximity to the wrist, this anomaly is related to falls, this type of fracture should be treated in a different and special way in children due to the continuous development of the radius and ulna bone, the type of treatment to be applied should be analyzed based on age and degree of injury where the distance of the fracture is evaluated. The current clinical study developed in a case of a male patient with a fracture of the anterior epiphysis of the radius bone, which has as objective the application of the Nursing Care Process by the nursing professional, where an analysis is made corresponding to the trauma originated in his bone structure, which presented an evolutionary picture of 3 days where he presented a fall of +- 1 meter of height, where the wrist was injured, which is edema, deformity and with hematomas for which it is the reason for consultation. The different analyses were carried out using Marjory Gordon's theory, NANDA, NIC, NOC to determine the altered functional patterns and based on that to carry out the nursing planning to carry out the activities, it is important to indicate that the Nursing Care Process was carried out in the appropriate way and was applied to the patient.